DIAGNOSIS OF PROSTATIC DISEASES IN DOGS - MENON, KIREN; DEVARAJ, M; KRISHNASWAMY, A; HONNAPPA, TG (The Indian Journal of Animal Reproduction, 2023)
The study outlines the various diagnostic procedures employed in diagnosis of prostatic diseases in dogs.Disorders of the prostate have a definite presence in old dogs and a cursory screening for the disease is mandatorywhen a suggestive clinical sign is noticed.
Keywords: Diagnosis; Prostatic Disease; Dogs